A GEOGRAPHICAL INFORMATION SYSTEM OF A WEB-BASED FOOD DELIVERY SERVICES - Aprilliyanto, Tofik; Fauzi, Muhammad Dzulfikar; Nuruzzaman, Muhammad Taufiq (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2015)
Food delivery services become more popular in Indonesia, which is proven by the number of restaurants that provide delivery services such as KFC, Mc Donald, and others. They are still using the phone to serve the customers. For customers, ordering by phone is less interactive since they cannot see the display of available menus with the prices and other details. For the cashiers, ordering by phone is also less effective since they have to write the menus, prices and addresses manually, whereas nowadays we need automation and the speed becomes a very important factor. This system is using Mobile Web technology and Geographical Information System (GIS), which with this technology the customers can order anywhere, and the order pages will be more interactive. For the cashiers, with this GIS, they do not need to record the data order manually. For food deliver, with the technology of GIS, food delivery processes will become easier due to the visualization of the location of customers, and they also can use the existing tracking features in GIS. The system implements the concept of client-server where the server website is used by restaurants, and mobile websites as client are used by customers for ordering food. The Web server has a notification ordering feature, administrator management, menus management, order management, suggestion management, restaurant management, and financial reports. Client's website has a food order feature, geolocation, and send suggestions features to the restaurant.